Between God and Hitler: military chaplains in Nazi Germany - Bergen, Doris L. (Cambridge University Press, 2025)
"During World War II, approximately 1,000 Christian chaplains accompanied Wehrmacht forces wherever they went, from Poland to France, Greece, North Africa, and the Soviet Union. Chaplains were witnesses to atrocity and by their presence helped normalize extreme violence and legitimate its perpetrators. Military chaplains played a key role in propagating a narrative of righteousness that erased Germany's victims and transformed the aggressors into noble figures who suffered but triumphed over their foes"--